The Joyful Life: An Existential-Humanistic Approach to Positive Psychology in the Time of a Pandemic - Robbins, Brent Dean (Frontiers in Psychology, 2021)
In the midst of a global pandemic, psychology has a duty to identify dispositional or character traits that can be cultivated in citizens in order to create resiliency in the face of profound losses, suffering and distress. Dispositional joy holds some promise as such a trait that could be especially important for well-being during the current pandemic and its consequences. The concept of the Joyful Life may operate as bridge between positive psychology and humanistic, existential, and spiritual views of the good life, by integrating hedonic, prudential, eudaimonic and chaironic visions of the good life. Previous phenomenological research on state joy suggests that momentary states of joy may have features that overlap with happiness but go beyond mere hedonic interests, and point to the experience of a life oriented toward virtue and a sense of the transcendent or the sacred. However, qualitative research on the Joyful Life, or dispositional joy, is sorely lacking. This study utilized a dialogical phenomenological analysis to conduct a group-based analysis of 17 volunteer students, who produced 51 autiographical narrative descriptions of the joyful life. The dialogical analyses were assisted by integration of the Imagery in Movement Method, which incorporated expressive drawing and psychodrama as an aid to explicate implicit themes in the experiences of the participants. The analyses yielded ten invariant themes found across the autobiographical narrative descriptions: Being broken, being grounded, being centered, breaking open, being uplifted, being supertemporal, being open to the mystery, being grateful, opening up and out, and being together. The descriptions of a Joyful Life were consistent with a meaning orientation to happiness, due to their emphasis on the cultivate of virtue in the service of a higher calling, the realization of which was felt to be a gift or blessing. The discussion examines implications for future research, including the current relevance of a joyful disposition during a global pandemic.